Overcoming limits of arbitrage: Theory and evidence - Hombert, Johan; Thesmar, David (Journal of Financial Economics, 2014)
Limits to arbitrage arise because financial intermediaries may face funding constraints when mispricing worsens. Using a model with limits to arbitrage, where we allow arbitrageurs to secure capital even in case of underperformance, we show that arbitrageurs that are more protected from withdrawals have more mean-reverting and volatile returns. Using data on hedge fund performance, we find robust support for these hypotheses: Funds with contractual impediments to withdrawals, and funds with performance-insensitive outflows, recover more quickly after a bad year and have more volatile returns. Our evidence is consistent with the idea that some hedge funds overcome the limits to arbitrage.